Pengaruh Pemahaman Wajib Pajak Muslim Atas Zakat Profesi Sebagai Pengurang Pkp Terhadap Keputusan Melaporkan Zakat Di Kpp Pratama Bengkalis - Dama, Dama Mustika (Brida Provinsi Jambi, 2023)
The purpose of this study was to test and analyze the effect of understanding of zakat as a deduction for taxable income (PKP) on zakat reporting at KPP Pratama Bengkalis. This research is an associative quantitative research using a causal relationship (cause and effect). The research subjects were Muslim taxpayers at KPP Pratama Bengkalis with sampling techniques using purposive sampling totaling 308 respondents. Data collection techniques in this study using questionnaires and literature (literature study). The results showed that there was a positive influence of Muslim taxpayers' understanding of zakat as a deduction for PKP on zakat reporting decisions. The calculated t value obtained is greater than the t table value, namely 29.909> 1.6498 and the Sig value. 0,000 < 0,05. The coefficient of determination (R Square) value of 0.745 concluded that the effect of Muslim taxpayers' understanding of zakat as a deduction for PKP (X) on zakat reporting decisions (Y) is 74.5% and the remaining 25.5% is influenced by variables or factors outside this study. Based on the results of this study, it is hoped that KPP and LAZ will play an active role in socializing zakat as a deduction for PKP on an ongoing basis so that more and more taxpayers as well as muzzaki know their rights, namely zakat as a deduction for PKP.